2004
DOI: 10.1177/0146167203256967
|View full text |Cite
|
Sign up to set email alerts
|

Implicit/Explicit Motive Discrepancies and Volitional Depletion among Managers

Abstract: The compensatory model of motivation and volition is based on the assumption that discrepancies between implicit and explicit motives lead to psychological conflict, and that resolution of this conflict requires volitional regulation and consumes volitional strength. This suggests that implicit/explicit motive discrepancies (IED) are responsible for decreases in volitional strength. A longitudinal field study with 82 managers was conducted to test this proposition. Results show that IED longitudinally predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
192
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(208 citation statements)
references
References 58 publications
(153 reference statements)
10
192
0
3
Order By: Relevance
“…Thus, motivational regulation states should save volitional resources. In support of this notion, I found that managers' implicit/explicit motive congruence was negatively associated with subsequent impairments in terms of depleted volitional strength (Kehr, 2004).…”
Section: Congruence Of Implicit Motives Explicit Motives and Abilitiesmentioning
confidence: 75%
See 2 more Smart Citations
“…Thus, motivational regulation states should save volitional resources. In support of this notion, I found that managers' implicit/explicit motive congruence was negatively associated with subsequent impairments in terms of depleted volitional strength (Kehr, 2004).…”
Section: Congruence Of Implicit Motives Explicit Motives and Abilitiesmentioning
confidence: 75%
“…A recent study examined volitional depletion among managers and found that implicit/ explicit motive discrepancies predicted decreased volitional strength and well-being and that the discrepancy/well-being relationship was fully mediated by reduced volitional strength (Kehr, 2004). Here, volitional strength, defined as the person's proficiency in using volitional strategies, is essentially identical to self-control strength (Muraven & Baumeister, 2000), volitional competence (Kuhl & Fuhrmann, 1998), and motivational skills (Kanfer & Heggestad, 1997 …”
Section: Proposition 5: Volitional Regulation Is Required To Compensamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if data collection involves field studies that require participation of hurried passengers, assessment of implicit motives by means of time consuming content-coding techniques might be too demanding and cause unacceptable drop-out rates. In fact, it is for exactly this reason that Kehr (2004) abandoned the PSE for the assessment of implicit motives. According to Kehr (2004), studies with management Running Head: ASSESSMENT OF NEED FOR AFFILIATION 13 samples caused unacceptable drop-out rates on the PSE.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is for exactly this reason that Kehr (2004) abandoned the PSE for the assessment of implicit motives. According to Kehr (2004), studies with management Running Head: ASSESSMENT OF NEED FOR AFFILIATION 13 samples caused unacceptable drop-out rates on the PSE. Therefore, he decided to use the MultiMotive-Grid (Sokolowski, Schmalt,Langens, & Puca, 2000) to assess implicit motives even though recent research puts the validity of grid techniques as measures of implicit motives into questions (Schultheiss et al, 2009).…”
Section: Discussionmentioning
confidence: 99%